Role of angiogenic transdifferentiation in vascular recovery - Cooke, John P.; Lai, Li (Frontiers in Cardiovascular Medicine, 2023)
Tissue repair requires the orchestration of multiple processes involving a multiplicity of cellular effectors, signaling pathways, and cell-cell communication. The regeneration of the vasculature is a critical process for tissue repair and involves angiogenesis, adult vasculogenesis, and often arteriogenesis, which processes enable recovery of perfusion to deliver oxygen and nutrients to the repair or rebuild of the tissue. Endothelial cells play a major role in angiogenesis, whereas circulating angiogenic cells (primarily of hematopoietic origin) participate in adult vasculogenesis, and monocytes/macrophages have a defining role in the vascular remodeling that is necessary for arteriogenesis. Tissue fibroblasts participate in tissue repair by proliferating and generating the extracellular matrix as the structural scaffold for tissue regeneration. Heretofore, fibroblasts were not generally believed to be involved in vascular regeneration. However, we provide new data indicating that fibroblasts may undergo angiogenic transdifferentiation, to directly expand the microvasculature. Transdifferentiation of fibroblasts to endothelial cells is initiated by inflammatory signaling which increases DNA accessibility and cellular plasticity. In the environment of under-perfused tissue, the activated fibroblasts with increased DNA accessibility can now respond to angiogenic cytokines, which provide the transcriptional direction to induce fibroblasts to become endothelial cells. Periphery artery disease (PAD) involves the dysregulation of vascular repair and inflammation. Understanding the relationship between inflammation, transdifferentiation, and vascular regeneration may lead to a new therapeutic approach to PAD.